A study of the sawtooth instability by means of external helical windings on the Tokoloshe tokamak - Nothnagel, G.(Gabriel) (Stellenbosch : Stellenbosch University, 2012)
Dissertation (Ph. D.) -- University of Stellenbosch, 1990.